How do small firms respond to tax schedule discontinuities? Evidence from South African tax registers - Wian Boonzaaier; Jarkko Harju; Tuomas Matikka; Jukka Pirttilä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
In this paper we study the effects of various tax schedule discontinuities on the behavior of small firms using high-quality and population-wide tax register data from South Africa. We use the bunching method to analyse how these discontinuities affect the firm-size distribution. We first examine how the value-added tax threshold affects the sales distribution of firms. We also study the effects of two separate corporate income tax rate kinks. We find sizable bunching at each of these thresholds. The elasticity estimates for the corporate tax kink points are large, ranging from 0.7 to 1.6, whereas the elasticity of the value added is below 0.1. We find some suggestive evidence that part of the response is driven by tax evasion.
Keywords: H21; H25; H32; O12; 330; developing countries; value-added tax; corporate tax; VAT threshold; corporate tax kink; bunching; small firms